Electrochemistry needs electrochemists: “goodbye to rotating discs” - Compton, RG; Sokolov, SV (Springer, 2023)
The essential need for expert, fully trained electrochemists in the successful application of the subject is illustrated with several examples including the use of rotating electrodes and impedance spectroscopy where the use of the techniques in “black box” mode non-experts is likely to lead to disappointment or embarrassment.